(untitled) (Swarnadwar, 2024)
For different obliqueness, ion velocity has been investigated numerically. Ions which are instreaming have to satisfy the criterion of Bohm-Chodura, to ensure the stability of plasma. Mean value as well as maximum/minimum amplitude is computed with different angles. Mean value of x-component is almost zero for all angles, whereas for y and z-component, mean value changes with different angles. On the other hand maximum amplitude almost changes for all angles. Ion velocity at presheath-sheath boundary, is affected by obliqueness of the field.